The application of Dublin Core Metadata Standard in UiTM libraries for Kedah, Shah Alam, and Kelantan campus: the benefits / Fauziah Abdul Wahid ... [et al.] - Abdul Wahid, Fauziah; Mohd Nordin, Nordiana; Mohammed Ghazali, Asmadi; Hassan, Rosli (2006)
Metadata can be defined, as ‘data-about-data’ were it describes the properties or characteristics of other data. It is considered as the latest concept in enhancing the capability of information storage and retrieval. In relation to this, the Dublin Core Working Groups has been formed and they have created Dublin Core Metadata Standard that consists of a set of 15 core optional elements for the description of document. DCMI Working groups are organised around specific problem domains. Working groups are formed and dissolved as dictated by the work at hand and the availability of expertise to accomplish such work. Dublin Core Metadata Initiative (DCMI) is an organisation dedicated to promoting the widespread adoption of interoperable metadata standards and developing specialised metadata vocabularies for describing resources that enable more intelligent information discovery systems. This research was conducted as an attempt to study the benefits of applying Dublin Core Metadata Standard in UiTM libraries for Kedah, Shah Alam, and Kelantan Campus. The main objective of this research is to clarify in depth about the Dublin Core Metadata Standard and the possibility of implementing this standard in generic organization of information for other types of printed and non-printed materials in this world. The result of the study shows that majority of respondents agreed that the application Dublin Core Metadata Standard would benefit generic organization of information in UiTM libraries. This may due to the fact that Dublin Core Metadata Standard is simple resource description and it is also a flexible standard that can interoperate with other system such as the library system.